Effect of Ramadan fasting on some biochemical and haematological parameters in Tunisian youth soccer players undertaking their usual training and competition schedule - Maughan, R. J.; Leiper, J. B.; Bartagi, Z.; Zrifi, R.; Zerguini, Y.; Dvorak, J. (Journal of Sports Sciences, 2008)
Competitive Muslim athletes often have to train and compete during the holy month of Ramadan when they abstain from food and drink from sunrise to sunset. In this study, we investigated the effect of Ramadan fasting on some biochemical and haematological parameters in 78 Tunisian junior male soccer players aged 16-19 years who continued their usual schedule of daily training and weekly competition. The study population was divided into four groups based on the time of day of sampling (am or pm) and on whether they were fasting (48 players: 28 am and 20 pm) or non-fasting (30 players: 14 am and 16 pm). Resting venous blood samples were collected approximately 3 weeks before Ramadan, after 2 and 4 weeks of Ramadan, and 3 weeks after the end of Ramadan. Some small, but statistically significant, modifications were observed in circulating concentrations of haemoglobin, ferritin, transferrin, creatinine and cortisol, but the mean values for all variables were always within the reference ranges. The minor changes observed during Ramadan may be explained by changes in patterns of food consumption, activity patterns and by hypohydration. The results suggest that the combination of the changes in eating time and frequency during Ramadan fasting, together with the continuation of normal training load, has no marked effect on the blood profiles of these adolescent athletes.